Three-year follow-up of aortic arch endovascular stent grafting with the Nexus device: results from a prospective multicentre study. (9th December 2022) - D'Onofrio, Augusto; Lachat, Mario; Mangialardi, Nicola; Antonello, Michele; Schelzig, Hubert; Chaykovska, Lyubov; Hill, Andrew; Holden, Andrew; Lindsay, Thomas; Ten Tan, Kong; Orrico, Matteo; Ronchey, Sonia; et al.
Abstract: OBJECTIVES: Endovascular aortic arch stent grafting with branched devices has shown initial promising results. The aim of this prospective, multicentre study was to evaluate 3-year outcomes of aortic arch stent grafting with NEXUS ® Aortic Arch Stent Graft System (Nexus), a single-branch, bi-modular, off-the-shelf aortic arch stent graft system in high-risk patients. METHODS: Patients treated with Nexus, either under the feasibility clinical study or as compassionate use procedures in 5 centres, were included in this study. The primary end point was overall survival. The secondary end points included the incidence of procedure-related unplanned intervention, stroke, paraplegia and endoleak. Clinical and radiologic follow-up was performed at each study site at 30 days, 6 months and on a yearly basis thereafter up to 3 years postoperatively. RESULTS: We analysed data from a total of 28 patients. The overall median follow-up was 1132 (interquartile range: 809–1537). There were no device or procedure-related deaths between 1 and 3 years. Overall survival at 1 and 3 years was 89% and 71%, respectively. The cumulative incidence of unplanned reintervention at 1 and 3 years was 11% and 29%, respectively. There were no reports of stroke, paraplegia, aneurysm rupture, myocardial infarction or new aortic valve insufficiency. In this study's 1–3 year follow-up period, 1 type Ib (4%), 1 type II (4%) and 2 type III (8%; between Nexus' distal end and Thoracic endovascular aortic repair (TEVAR) extensions) endoleak were detected. CONCLUSIONS: Endovascular aortic arch exclusion with the single-branch, off-the-shelf Nexus system provides promising clinical and radiologic results at 3-year follow-up in a high-risk patient cohort. Abstract : The standard treatment for patients with aortic arch disease is represented by surgical aortic arch replacement, with or without frozen elephant trunk (FET) [1].